2018
DOI: 10.1017/s0373463318000504
|View full text |Cite
|
Sign up to set email alerts
|

Robust Ship Tracking via Multi-view Learning and Sparse Representation

Abstract: Conventional visual ship tracking methods employ single and shallow features for the ship tracking task, which may fail when a ship presents a different appearance and shape in maritime surveillance videos. To overcome this difficulty, we propose to employ a multi-view learning algorithm to extract a highly coupled and robust ship descriptor from multiple distinct ship feature sets. First, we explore multiple distinct ship feature sets consisting of a Laplacian-of-Gaussian (LoG) descriptor, a Local Binary Patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…The histogram of oriented gradient (HOG), local binary pattern. (LBP), and Gabor feature descriptors are commonly used to identify target contours for the purpose of helping varied trackers obtain high tracking accuracy which indeed have enjoyed huge success in many object tracking applications [10]. The Canny feature descriptor can effectively overcome the edge variation challenge (caused by wave imaging changes) [37], and the LoG descriptor is a popular blob-detector providing a complementary description of ship shape [38].…”
Section: Ship Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histogram of oriented gradient (HOG), local binary pattern. (LBP), and Gabor feature descriptors are commonly used to identify target contours for the purpose of helping varied trackers obtain high tracking accuracy which indeed have enjoyed huge success in many object tracking applications [10]. The Canny feature descriptor can effectively overcome the edge variation challenge (caused by wave imaging changes) [37], and the LoG descriptor is a popular blob-detector providing a complementary description of ship shape [38].…”
Section: Ship Feature Extractionmentioning
confidence: 99%
“…Previous studies mainly employed automatic identification systems (AIS) to track ships sailing in inland waterways [4][5][6], and several techniques (e.g., synthetic aperture radar (SAR), long-range identification and tracking (LRIT)) have been integrated to further enhance ship tracking accuracy [7][8][9][10]. More specifically, maritime traffic participants can track ship positions with the LRIT technique over large time intervals (usually every six hours) when the ship travels far away from coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al used the association rules to determine crucial maritime accident contributory factors and mutual coupled effects on the ship detention incident [11]. Similar studies can be found in [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…e size of the adhesion coefficient mainly depends on the condition of the road surface and the tire, and the road surface factors mainly include the type of road surface, roughness and dryness, and humidity. e tire factor is mainly the tread pattern of the tire, that is, the type and depth of the tread [22][23][24].…”
Section: Road Factorsmentioning
confidence: 99%